2012
DOI: 10.1111/j.1524-4725.2011.02199.x
|View full text |Cite
|
Sign up to set email alerts
|

Earlobe Keloids: Classification According to Gross Morphology Determines Proper Surgical Approach

Abstract: This novel classification for earlobe keloids can lead to a better understanding of the different types of earlobe keloids and inform decisions regarding surgical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 18 publications
(35 reference statements)
0
45
0
Order By: Relevance
“…Baseline keloids treatment protocols are described in our previous studies. 3,7 The primary purpose of this study was to determine the clinical relevance of our proposed variables (patient age, age of onset, sex, recurrence, anatomical locations, primary vs secondary keloids, and family history of keloids) on the pattern of clinical presentation and multiplicity of keloids. The secondary purpose of our study was to analyze and compare the characteristics of patients with primary keloids and secondary keloids as separate groups.…”
Section: Methodsmentioning
confidence: 99%
“…Baseline keloids treatment protocols are described in our previous studies. 3,7 The primary purpose of this study was to determine the clinical relevance of our proposed variables (patient age, age of onset, sex, recurrence, anatomical locations, primary vs secondary keloids, and family history of keloids) on the pattern of clinical presentation and multiplicity of keloids. The secondary purpose of our study was to analyze and compare the characteristics of patients with primary keloids and secondary keloids as separate groups.…”
Section: Methodsmentioning
confidence: 99%
“…[3] Case Report A 25-year-old male patient presented with a relapsing earlobe keloid. The primary injury was earlobe piercing.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the consequences of keloids including cosmetic deformity and psychological trauma, complete cure without recurrence is one of the most important considerations to physicians as well as patients [2,3]. As sessile-type keloids are not sharply demarcated and marginal recurrences of sessile-type keloids are not infrequent in the clinical practice, we suggested that pedunculated-type keloids be the best candidate for the treatment with laser [4].…”
mentioning
confidence: 99%